ANTI-MYCOBACTERIUM TUBERCULOSIS STRAIN H37RV AND IRON CHELATION ACTIVITY OF SAPPAN WOOD EXTRACT (CAESALPINIA SAPPAN L.) IN VITRO - Safitri, Ratu; Indrawati, Ida; Syamsunarno, Mas Rizky A A; Ghozali, Mohammad; A Gani, Basri; Panigoro, Ramdan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to determine anti-Mycobacterium tuberculosis (MTB) strain H37Rv and iron chelation activities of sappan wood extract (SWE). Methods: The evaluation of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) by proportion methods. Whereas the iron chelate in Lowenstein–Jensen (LJ) medium as the indicator of Mycobacterium growth and SWE effect. Results: The SWE has bacteriocidal to MTB of 10−3 and 10−5 dilutions in of all concentrations (250, 500, 750, 1000, 2000, 4000, 8000, and 16000 part per millions [ppm]) also bacteriostatic in concentration 50 and 100 ppm. Conclusion: The SWE at 100 ppm could inhibit 87% of the MTB in 10−3 and 10−5 dilutions, respectively, also to reduce to growth the colony of MTB, and has chelating effects of iron expression of LJ medium and MTB.